Fabricating science and technology studies in the Philippines - Anderson, Warwick (Philippine Studies: Historical and Ethnographic Viewpoints, 2023)
This essay is a reflection on the development of reformist and critical science studies in the Philippines. Furthermore, it speculates on the possibility of "Philippines as method" in science and technology studies. This approach represents further specifications and situating of diverse regional ontologies - and critical theories - of science and technology.